Withaferin A Associated Differential Regulation of Inflammatory Cytokines - Dubey, Seema; Yoon, Hyunho; Cohen, Mark Steven; Nagarkatti, Prakash; Nagarkatti, Mitzi; Karan, Dev (Frontiers in Immunology, 2018)
A role of inflammation-associated cytokines/chemokines has been implicated in a wide variety of human diseases. Here, we investigated the regulation of inflammatory cytokines released by monocyte-derived THP-1 cells following treatment with the dietary agent withaferin-A (WFA). Membrane-based cytokine array profiling of the culture supernatant from ATP-stimulated WFA treated THP-1 cells showed differential regulation of multiple cytokines/chemokines. A selected group of cytokines/chemokines (IL-1, CCL2/MCP-1, GM-CSF, PDGF-AA, PTX3, CST3, RLN2, TNFRSF8/CD30, and ACRP30) was validated at the transcription level using qPCR. In silico analysis for transcriptional binding factors revealed the presence of nuclear factor-kappa B (NF-B) in a group of down-regulated cytokine gene promoters. WFA treatment of THP-1 cells blocks the nuclear translocation of NF-kB and corresponds with the reduced levels of cytokine secretion. To further understand the differential expression of cytokines/chemokines, we showed that WFA alters the nigericin-induced co-localization of NLRP3 and ASC proteins, thereby inhibiting caspase-1 activation, which is responsible for the cleavage and maturation of pro-inflammatory cytokines IL-1 and IL-18. These data suggest that dietary agent WFA concurrently targets NF-B and the inflammasome complex, leading to inhibition of IL-1and IL-18, respectively, in addition to differential expression of multiple cytokines/chemokines. Taken together, these results provide a rationale for using WFA to further explore the anti-inflammatory mechanism of cytokines/chemokines associated with inflammatory diseases.